On Parameters Estimation of Lomax Distribution under General Progressive Censoring. (5th June 2013) - Al-Zahrani, Bander; Al-Sobhi, Mashail
Abstract : We consider the estimation problem of the probabilityS = P ( Y < X ) for Lomax distribution based on general progressive censored data. The maximum likelihood estimator and Bayes estimators are obtained using the symmetric and asymmetric balanced loss functions. The Markov chain Monte Carlo (MCMC) methods are used to accomplish some complex calculations. Comparisons are made between Bayesian and maximum likelihood estimators via Monte Carlo simulation study.